2008
DOI: 10.1002/arch.20281
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of proteins involved in ecdysone and juvenile hormone signal transduction

Abstract: Ecdysteroids and juvenile hormones (JH) regulate a variety of developmental, physiological, behavioral, and metabolic processes. Ecdysteroids function through a heterodimeric complex of two nuclear receptors, ecdysone receptor (EcR) and ultraspiracle (USP). An 85 kDa protein identified in Drosophila melanogaster methoprene‐tolerant (Met) mutant binds to JH III with high affinity, and the mutant flies are resistant to juvenile hormone analog (JHA), methoprene. Reporter assays using the yeast two‐hybrid system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
(43 reference statements)
3
27
1
2
Order By: Relevance
“…However, the interaction between Met1 and USP1 may not rely on JH regulation because the overexpressed Met1 is co-immunoprecipitated with nonphosphorylated USP1 in DMSO-treated cells also. The 20E-or JH hormoneindependent interactions between Met and USP and between Met and EcRB1 has been reported in D. melanogaster (Bitra & Palli 2009) and B. mori (Guo et al 2012) respectively. Therefore, Met1 might repress 20E pathway gene transcription by repressing the formation of EcRB1/USP1 transcription complex and its binding to EcRE.…”
Section: Met1 Represses the Transcription Of A Set Of 20e-responsive mentioning
confidence: 87%
See 1 more Smart Citation
“…However, the interaction between Met1 and USP1 may not rely on JH regulation because the overexpressed Met1 is co-immunoprecipitated with nonphosphorylated USP1 in DMSO-treated cells also. The 20E-or JH hormoneindependent interactions between Met and USP and between Met and EcRB1 has been reported in D. melanogaster (Bitra & Palli 2009) and B. mori (Guo et al 2012) respectively. Therefore, Met1 might repress 20E pathway gene transcription by repressing the formation of EcRB1/USP1 transcription complex and its binding to EcRE.…”
Section: Met1 Represses the Transcription Of A Set Of 20e-responsive mentioning
confidence: 87%
“…In Drosophila, the overexpression of Met in fat body results in precocious and enhanced programmed cell death and cell dissociation (Liu et al 2009). Met can also interact with EcR and USP in insect cells in an ecdysteroid or in a JH-regulation-independent manner, suggesting that the interaction among Met, EcR, and USP mediates the crosstalk between these two important hormones (Bitra & Palli 2009). Therefore, the basic function of Met in various insects is not really clear.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the molecular roles of Met in JH signaling, a number of proteins have been tested in vitro or in the cultured insect cells for their abilities to bind Met (9,28,32). The protein interactions with Met were largely independent of the presence of JH, or even repressed by JH.…”
Section: Discussionmentioning
confidence: 99%
“…Os miRNAs evoluíram como uma classe de moléculas reguladoras de inúmeros processos biológicos em eucariotos, como proliferação celular, diferenciação, apoptose, resposta a estresse, tumorigênese, entre outros (Banerjee & Slack, 2002;Banerjee et al, 2005;Bartel, 2004;2009). A busca por miRNAs, potenciais reguladores de jhe, resultou em 22 candidatos, dos quais apenas 9 com função já descrita na literatura.…”
Section: Potenciais Mirnas Reguladores De Jheunclassified
“…usp is an ortholog of vertebrates retinoid-X receptor (RXR) (Yao et al, 1992(Yao et al, , 1993, considered at first as an orphan NR, but some studies have suggested it as a JH receptor, besides acting as part of ecdysteroid receptor (Xu et al, 2002;Barchuk et al, 2004), and indicating a cross-talk between ecdysteroid and JH action (Bitra and Palli, 2009). In Drosophila, EcR gives rise to three different isoforms, EcR-A, EcR-B1 e EcR-B2 (Yao et al, 1993;Talbot,1993), differentially expressed in a tissue-and stage-specific manner (Robinow et al, 1993;Truman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%